Transient characteristics of mobile transformer vehicle bypass operation - Zhou, Lei; Feng, Xiao; Chen, Xi; Fu, Hongquan; Bian, Changhao; Jing, Yang; Wu, Shaocheng (Frontiers in Energy Research, 2023)
The bypass operation method of mobile transformer vehicles is a common method for the maintenance or replacement of transformers in distribution lines. Using the bypass operation method could avoid power outages and ensure the reliability of electricity consumption. However, the transient characteristics of mobile transformer vehicles connected to the grid can have an impact on their power quality. In response to this problem, this study built a model based on MATLAB/Simulink to model the process of grid connection. The simulation analyzed the current and voltage waveforms of the transient process of grid connection. Moreover, a combination of time-domain and frequency-domain analysis was used to analyze the transient overvoltage and overcurrent conditions of the grid connection. Finally, the effects of two overcurrent suppression methods, adjustment of the closing angle method and the series closing resistance method, were analyzed. These studies provide theoretical guidance for engineering applications, which could strengthen the stability of the distribution network.